2019
DOI: 10.1029/2019jb018377
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Stress State of Seismogenic Faults in Oklahoma and Southern Kansas Based on an Improved Stress Map

Abstract: Fault location and geometry are critical considerations in the reactivation of preexisting faults. Here, we combine relocated earthquake catalogs and focal mechanisms to delineate seismogenic faults in Oklahoma and southern Kansas and analyze their stress state. We first identify and map seismogenic faults based on earthquake clustering. We then obtain an improved stress map using 2,047 high‐quality focal mechanisms. The regional stress map shows a gradual transition from oblique normal faulting in western Okl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 74 publications
2
24
0
Order By: Relevance
“…Zoback and Townend (2001) suggested that intraplate crust is in a state of failure equilibrium based on worldwide borehole observations. Based on a high-resolution stress map for Oklahoma (Qin et al, 2019), the orientation of the Cushing fault that hosted the M5 earthquake is optimally oriented for failure ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Zoback and Townend (2001) suggested that intraplate crust is in a state of failure equilibrium based on worldwide borehole observations. Based on a high-resolution stress map for Oklahoma (Qin et al, 2019), the orientation of the Cushing fault that hosted the M5 earthquake is optimally oriented for failure ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the structural inheritance of basement fault systems by the sedimentary sequences may explain the recent widespread seismogenic strike‐slip reactivation in north‐central Oklahoma, attributed to sedimentary‐to‐basement migration of fluids (e.g. Kolawole, Johnston, et al, 2019; Qin, Chen, Carpenter, & Kolawole, 2018; Qin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…First, the area hosts the occurrence of sporadic and widespread wastewater injection-induced seismicity (e.g., Kolawole et al, 2019b). The Arbuckle Group is the primary zone of wastewater disposal, and the Precambrian Basement hosts most of the resulting induced seismicity (e.g., Kolawole et al, 2019). Second, the shelf area hosts the STACK ("Sooner Trend, Anadarko, Canadian and Kingfisher") and Mississippi Lime Plays, which are currently some of the most active unconventional hydrocarbon exploration plays in North America (e.g., Yee et al, 2017).…”
Section: 2mentioning
confidence: 99%
“…However, we do not rule out the possibility. Both sub-horizontal (sill) and sub-vertical (dike) mafic sheet intrusions occur in the outcrop exposures of the Oklahoma basement, where the sills commonly branch out from the dikes (e.g., Lidiak et al, 2014;Kolawole et al, 2019). However, the absence of dike-related reflections in our seismic dataset may be explained by the inherent difficulty of seismic reflection imaging of dikes (e.g., Zaleski et al, 1997;Wall et al, 2010;Phillips et al, 2018).…”
Section: Intrabasement Deformation and Structural Inheritance In The Anadarko Shelfmentioning
confidence: 99%
See 1 more Smart Citation